The medieval Turks - Hillenbrand, Carole, 1943- (Edinburgh)
xiv, 397 sayfa
Keywords: “This volume explores the impact of the Turks on the medieval Islamic world. It covers themes such as nomadism, shamanism, clan and social structure, the role of women, military expertise, engagement with Islamic orthodoxy and the daily interface between Turks and non-Turks. The Medieval Turks is publishing alongside two further volumes of Carole Hillenbrand's collected papers: Classical Islam and Islam and the Crusades.” --